Experimental and numerical studies on heat transfer enhancement for air conditioner condensers using a wavy fin with a rectangular winglet - Chimres, Nares; Chittiphalungsri, Thunyawat; Asirvatham, Lazarus Godson; Dalkilic, Ahmet Selim; Mahian, Omid; Wongwises, Somchai (KOREAN SOC MECHANICAL ENGINEERS, 2020)
The air side thermal performance of wavy fins with rectangular winglets are studied using experimental and numerical methods. The following parameters are selected for investigation: the attack angle, placed location, span and length of the rectangular winglet. The results show that all parameters affect the thermal performance of the air side. The best configurations of the winglet that provide the maximum j/f((1/3))for both winglet lengths are the 3.5 mm horizontal distance, 7 mm vertical distance, 60 degrees attack angle and 1.25 mm winglet span. Moreover, the thermal performance comparisons between the optimal design of the wavy fin with winglet and normal wavy fin are reported. Wavy fins with winglets provide a larger heat transfer coefficient, pressure drop and j/f((1/3))than those of normal wavy fins. For the j/f((1/3))comparison, wavy fins with winglets provide a j/f((1/3))greater than that of normal wavy fins by 5.4-14.6 %, with the Reynolds number ranging from 1650 to 4423.
Keywords: Condenser; Heat transfer enhancement; CFD; Wavy fin; Vortex generator; Rectangular winglet; PLATE-FIN; VORTEX GENERATORS; SIDE PERFORMANCE; FLUID-FLOW; THERMOHYDRAULIC PERFORMANCE; FRICTION CHARACTERISTICS; FLAT TUBE; EXCHANGERS; CONVECTION; VORTICES; Engineering